2012
DOI: 10.1016/j.carj.2011.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2- and 3-Dimensional Shoulder Ultrasound to Magnetic Resonance Imaging in a Community Hospital for the Detection of Supraspinatus Rotator Cuff Tears with Improved Worktime Room Efficiency

Abstract: 3D US of the shoulder is as accurate as 2D US when compared with MRI for the diagnosis of full- and partial-thickness supraspinatus rotator cuff tears, and 3D US examination significantly reduced the time between the initial scan and the radiologist interpretation, ultimately improving workplace efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 33 publications
1
23
0
2
Order By: Relevance
“…In this study, MRA has a sensitivity of 0.81 and speci city of 0.96 for detecting articular-sided PTRCTs; however, MRI shows a sensitivity of 0.78 and speci city of 0.97 in detection of the articular-sided PTRCTs. The differences in speci city and sensitivity between MRA and MRI are quite small, and that may be a good reason to avoid the potential risk/cost of MRA, this result is in accordance with a prospective study that the sensitivity and speci city of MRA were improved only by 3-4% when compared with MRI [36].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, MRA has a sensitivity of 0.81 and speci city of 0.96 for detecting articular-sided PTRCTs; however, MRI shows a sensitivity of 0.78 and speci city of 0.97 in detection of the articular-sided PTRCTs. The differences in speci city and sensitivity between MRA and MRI are quite small, and that may be a good reason to avoid the potential risk/cost of MRA, this result is in accordance with a prospective study that the sensitivity and speci city of MRA were improved only by 3-4% when compared with MRI [36].…”
Section: Discussionsupporting
confidence: 89%
“…MRA has a good diagnostic performance mainly depending on the objective evidence of the leakage of contrast agent, accompanied by a good anatomic resolution and subtle defects depicted by contrast agents [33,34]. Nonetheless, MRA, as an invasive diagnosis modality, has many disadvantages and limitations, including a longer examination time, increased risk of infection and adverse complication [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…However, MRA, usually with a longer examination time, will bring the infections and adverse complications because of an invasive procedure of the injection of contrast agent [52]. Moreover, the classification and basic properties of the contrast agent will have a huge effect on the diagnostic value of MRA [53]. Numerous studies reported that false positive cases were often triggered by the inflamed tendon [54], and false negative cases were caused by the failure of contrast to pass into the bursa [29, 33].…”
Section: Discussionmentioning
confidence: 99%
“…Previous authors have demonstrated that US and MRI have comparable and high accuracy for detecting full-and partial thickness tears in rotator cuff(24)(25)(26). MRI gives more information about muscle degeneration, the under acromion area and other coexisting pathologic process.…”
mentioning
confidence: 99%
“…We chose ultrasound because it is dynamic, less invasive and more sensitive than MRI in assessment of rotator cuff pre-insetional tendinopathy. Other studies carried out in volleyball, basketball, baseball and swimmers used US to evaluate the rotator cuff tendinopathy(1,(24)(25)(26)(27).The international protocol proposed by European Society of Musculoskeletal Radiology (ESMR) was adopted because considered as the most detailed and effective protocol for analysis and the comparison with other overhead-throwing studies (17). 61% of patients had a higher degeneration of the dominant supraspinatus compared with non-dominant (P< .05).…”
mentioning
confidence: 99%